2023
DOI: 10.1227/neu.0000000000002340
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Postoperative Cerebral Venous Sinus Thrombosis After Posterior Fossa Tumor Surgery: Incidence, Risk Factors, and Therapeutic Options

Abstract: BACKGROUND: Cerebral venous sinus thrombosis (CVST) is a known complication of posterior fossa surgery near the sigmoid and transverse sinus. The incidence and treatment of postoperative asymptomatic CVST are controversial. OBJECTIVE: To analyze incidence, risk factors, and management of asymptomatic postoperative CVST after posterior fossa tumor surgery. METHODS: In this retrospective, single-center study, we included all patients who underwent posterior fossa tumor surgery in the semisitting position between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…1,4 Mechanical provoking factors such as head trauma, neurosurgical procedures, and compressive lesions such as meningiomas impinging on venous sinuses are also associated with CVT. 1,4,21…”
Section: Predisposing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4 Mechanical provoking factors such as head trauma, neurosurgical procedures, and compressive lesions such as meningiomas impinging on venous sinuses are also associated with CVT. 1,4,21…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…Women with a history of VTE appear to have an increased risk of thrombotic events (ie, deep venous thrombosis, pulmonary embolism) in future pregnancies. 64 A systematic review comprising 17 studies and 393 pregnancies found a recurrence rate of 8 per 1000 pregnancies (95% CI, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The rate of noncerebral VTEs was 22 per 1000 pregnancies (95% CI, 11-43).…”
Section: Future Pregnancies and Recurrencementioning
confidence: 99%
“…Patients undergoing posterior fossa surgery for cerebellopontine angle tumors are largely retained at increased risk for the development of CVST [1,2,15,21].…”
Section: Infratentorial Cvstmentioning
confidence: 99%
“…Besides to be a spontaneous event in several systemic conditions such as infection, malignancies, hematologic disorders, trauma, etc., cerebral venous sinus thromboses (CVST) can be also complications of neurosurgical interventions, especially in case of lesions or surgical approaches involving the dural sinuses with a reported incidence estimated between 5% and 12% [3,6,15,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation